Caregiver Involvement as a Determinant of Learning Commitment among Orphanage Students - Friska Harlistia; Muhammad Ja’far Nashir (Madrasah Tsanawiyah DDI Cilellang, 2025)
Orphanages are expected to provide emotional support and foster learning motivation, yet many residents face psychological barriers that undermine their study commitment. This study aims to examine the influence of caregiver involvement on the learning commitment of orphanage students. A quantitative approach was employed by distributing questionnaires to 30 respondents, followed by simple linear regression and t-tests to analyze variable effects. The findings indicate that caregiver involvement was rated as good, while students’ learning commitment was rated as very good. Caregiver involvement had a positive and significant effect on learning commitment. Theoretically, these findings reinforce social support theory and social-cognitive motivation theory, both of which emphasize the role of significant figures in shaping students’ intrinsic motivation. Practically, the study recommends that caregivers enhance consistency in academic monitoring and intensify learning guidance. From a policy perspective, the results may inform orphanage managers and government agencies in designing more systematic academic mentoring programs. The study is limited by the relatively small sample size, reliance on closed-ended questionnaires, and its focus on a single orphanage. Future research with broader samples and data triangulation is recommended to obtain a more comprehensive understanding of the determinants of students’ learning commitment.